The Effectiveness of the Implementation of the Basic Foodstuffs Assistance Program in Bagjasari Village, Cikijing Subdistrict, Majalengka Regency - Nowaf Fathullah Abdurohman; Hery Nariyah (Jurnal Impresi Indonesia, 2026)
The Basic Food Assistance Programme is a social protection policy developed by the government to support the food needs of low-income families with minimal household expenses. The success of this programme depends greatly on its implementation, especially at the village level, which is the front line of public policy implementation. This research aims to analyse the effectiveness of the implementation of the Food Assistance Programme in Bagjasari Village, Cikijing Sub-district, Majalengka Regency. The current study employed a qualitative approach with a descriptive method. Data collection involved in-depth interviews, field observations, and document analysis with village officials, Food Assistance Programme facilitators, and beneficiary families. Data analysis was conducted interactively through the stages of data reduction, data presentation, and drawing of conclusions. The research analysis framework refers to the concept of programme effectiveness consisting of five main indicators, namely understanding of the programme, accuracy of targeting, timeliness, accuracy of implementation, and achievement of objectives. The results of this study show that the implementation of the Food Assistance Programme in Bagjasari Village is considered quite effective. The objectives and mechanisms of the programme were generally well understood by the beneficiaries, and the assistance was fairly well targeted. However, some challenges were also noted, including delays in distribution during certain periods and the need for periodic updates of beneficiary data. To make the Food Assistance Programme more effective at the village level, it is therefore necessary to improve coordination among implementers, strengthen oversight, and update the data regularly.